Low-Level Laser Therapy for Rheumatoid Arthritis: A Review of Experimental Approaches: Low-Level Laser Therapy as a Complementary Treatment for Rheumatoid Arthritis - Hossein-khannazer, Nikoo; Arki, Mandana Kazem; Keramatinia, Aliasghar; Rezaei Tavirani, Mostafa (Journal of Lasers in Medical Sciences, 2022)
Introduction: Rheumatoid arthritis (RA) is an inflammatory and autoimmune disorder that is characterized by joint inflammation, pain, physical disability, and morning stiffness. In the present study, the effect of low-level laser therapy (LLLT) on RA was reviewed. Methods: “Low-level laser therapy”, “rheumatoid arthritis disease”, and “photobiomodulation” keywords were searched in Google Scholar, PubMed, and Medline. Results: A literature survey led to a discussion about the immunology of the RA, laser therapy, mechanism of LLLT action, and anti-inflammatory and immunomodulatory properties of LLLT. Conclusion: It was concluded that LLLT could improve RA patients’ quality of life, reduce pain, and enhance physical movement.